Inpatients' Perception of Patient-Centered Care in Guangdong Province, China: A Cross-Sectional Study - Ling-ming Zhou; Richard Huan Xu; Yan-hua Xu; Jing-hui Chang; Dong Wang (SAGE Publishing, 2021)
This study aimed to investigate the perceptions of patient-centered care (PCC) among inpatients in Guangdong Province (GD), China. Based on these perspectives, we sought to understand existing PCC practices in medical institutions and identify the impacts of inpatients' sociodemographic status on their perceived PCC. A self-developed PCC questionnaire was used to investigate inpatients' perceptions of PCC. A cross-sectional survey was conducted in nine tertiary-level hospitals across five cities in GD. Descriptive statistics was used to describe the levels of PCC in GD. The differences in PCC levels across different sociodemographic groups were assessed using analysis of variance and multivariate linear regression. Valid responses were provided by 1863 inpatients. The mean overall PCC score was 8.58 (standard deviation [SD] = 1.36); inpatients from the Pearl River Delta and eastern GD area reported significantly higher scores than those from western and northern GD area ( P <.01). Inpatients from rural areas tended to report lower PCC scores than their urban counterparts. Among the PCC questionnaire sub-domains, inpatients scored highest and lowest in "patient experience" (mean = 8.96, SD = 1.34) and "medical insurance" (mean = 7.93, SD = 2.05), respectively. This study provided a comprehensive overview of inpatients' perceptions of PCC in the public healthcare system in GD, China. Our findings highlighted that a majority of inpatients were satisfied with the PCC in public healthcare system; however, a significant discrepancy between inpatients with different sociodemographic status remained.